Accounting Information Quality, Interbank Competition, and Bank Risk-Taking - Corona, Carlos; Nan, Lin; Zhang, Gaoqing (The Accounting Review, 2015)
ABSTRACT We study the interaction between interbank competition and accounting information quality and their effects on banks' risk-taking behavior. We identify an endogenous false-alarm cost that banks incur when forced to sell assets to meet capital requirements. We find that when the interbank competition is less intense, an improvement in the quality of accounting information encourages banks to take more risk. Keeping the banks' investments in loans constant, the provision of high-quality accounting information reduces the false-alarm cost of assets sales and improves the discriminating efficiency of the capital requirement policy. When considering the banks' endogenous investment decisions, however, this improvement in discriminating efficiency causes excessive risk-taking, because banks respond by competing more aggressively in the deposit market, and the increase in deposit costs motivates banks to take more risk. Our paper shows that improving information quality increases risk-taking with mild competition, but has no effect under fierce competition.